Banal Politik Transaksional Para Pemilih (Tinjauan Psikologis) - Haressa Lintang Rizkika; Hikmatul Ummah; Aidina Winona Raider; Erna Ipak Rahmawati (Universitas Muhammadiyah Jember, 2019)
Organizing a democratic party - general election (Election) - in Indonesia today is no stranger to the term 'money politics' or transactional politics. Ideally, a political choice in a democratic party is based on an interest in the candidate's vision and mission or based on shared ideology and is carried out in accordance with the values and norms that exist in society. But in fact, transactional politics have been commonplace from the biggest political event to the lowest level or in other terms to be 'banal' or considered normal in our society. This study uses a qualitative approach with a phenomenological study in which the results are a description of the psychological dynamics of transactional political actors in this case the voters. The results obtained that in the review of the dynamics field theory of the principals began with a motivation symbolized as a V (Vector) towards the goal in the form of money without significant obstacles or permeable bondaries in the psychological environment of the research subject. In the typology of the personal living space symbolized as (P) believing that; 1) Giving is considered a representation of prosocial actions; 2) Giving is something that is considered not violating the values and norms of individuals and society; 3) Individuals have the resources and opportunity to conduct transactional politics.